2020
DOI: 10.1111/jam.14673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofPantoea eucalyptiFBS135 for pine (Pinus massoniana) growth promotion and its genome analysis

Abstract: Aims Pinus massoniana is one of the most widely distributed forest plants in China. In this study, we isolated a bacterial endophyte (designated FBS135) from apical buds and needles of P. massoniana. Investigations were performed to understand the effects of the strain on pine growth, its genomic features and the functions of the plasmids it carries. Methods and Results Based on its morphological features and 16S rRNA sequence, strain FBS135 was primarily identified as Pantoea eucalypti. We found that FBS135 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Genome and plasmid information of the two strains have been summarized in Table 2 . Different from the two strains, FBS135 has four plasmids, one (pPant4) of which seems to be responsible and indispensable for its growth [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genome and plasmid information of the two strains have been summarized in Table 2 . Different from the two strains, FBS135 has four plasmids, one (pPant4) of which seems to be responsible and indispensable for its growth [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the genome information, we precisely determined the taxonomic status of Pantoea sp. FBS135, an endophyte isolated from Pinus massoniana with evidenced ability of promoting pine growth and stress tolerance [ 17 ]. We also demonstrated that FBS135 can tolerate an extremely low nitrogen environment without fixing nitrogen in the air.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent times, studies of the complete genomes of PGPR are elucidating the genes that explain the plant growth promoting activities and the plant-bacteria dialog in the rhizosphere (Song et al, 2012;Usha et al, 2015;Bhattacharyya et al, 2017). Accordingly, the draft genomes of several Pantoea strains with PGPR activities have been compared (Bruto et al, 2014;Palmer et al, 2018;Song et al, 2020). In general these microorganisms show wide versatility and adaptability, together with multiple PGP activities such as phosphate solubilization, nitrogen fixation, ACC deaminase activity, auxins production and secretion of siderophores (Shariati et al, 2017;Chen and Liu, 2019;Luziatelli et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%